PENGEMBANGAN MEDIA PEMBELAJARAN ORASI PECAH BERBASIS FLIP PDF CORPORATE EDITION - Ana Istiani; Suminto Suminto; Trisnawati Trisnawati; Robia Astuti; Gita Fadila Rahmawati; Nadia Zeniarti (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The availability of an internet network in schools makes it possible for teachers to design web-based learning. This is in line with the development of the digital era which encourages classroom learning to transform from the use of printed books to digital books. Broken Oration Learning Media is a flip-based E-module, PDF corporate edition, which is a web-based learning media that is declared suitable and effective for use by experts. The Development Research method used is the 4-D method, namely define, design, develop and disseminate. The research trial subjects were 20 class V students of SD Negeri 1 Wates. The data collection techniques used are expert assessments, questionnaires and learning outcomes tests. The data analysis techniques used are feasibility tests based on expert assessments, effectiveness tests based on user responses, and learning outcomes. The results of the research show that the learning media for broken oration based on expert assessment received an average score of 4.6, which means that the learning media for broken oration is feasible and effective to use. Meanwhile, the results of data analysis from testing the effectiveness of e-module media based on student responses obtained a score of 91.80% who responded positively, and student learning results obtained a classical completeness score of 85.18%.